2016
DOI: 10.4254/wjh.v8.i34.1497
|View full text |Cite
|
Sign up to set email alerts
|

Fractional excretion of sodium in hepatorenal syndrome: Clinical and pathological correlation

Abstract: AIMTo determine the accuracy of fractional excretion of sodium (FeNa) in the diagnosis of hepatorenal syndrome (HRS).METHODSEighty-eight liver transplantation candidates with renal dysfunction and/or proteinuria were included in the study sample. The baseline characteristics of the patients were obtained. All the 88 patients underwent iothalamate glomerular filtration rate testing, 24-h urine collection for urinary sodium and protein excretions, random urine for sodium and creatinine testing, and percutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Some experts have used urinary sodium (>40 mEq/L), fractional excretion of sodium (FeNa >2%), and low urine osmolality (<400 mOsm/L) as suggestive of ATN; however, urinary sodium can be elevated secondary to diuretics, frequently used in this group of patients with large volume ascites. 55 Conversely, low FeNa has also been observed in patients with biopsy proven ATN, 56 so urinary sodium and FeNa are no longer part of the diagnostic criteria of AKIHRS. Studies in patients without liver disease have found that fractional excretion of urea is superior to FeNa in differentiating AKIHRS from ATN in patients taking diuretics.…”
Section: Differential Diagnosis and Biomarkersmentioning
confidence: 99%
“…Some experts have used urinary sodium (>40 mEq/L), fractional excretion of sodium (FeNa >2%), and low urine osmolality (<400 mOsm/L) as suggestive of ATN; however, urinary sodium can be elevated secondary to diuretics, frequently used in this group of patients with large volume ascites. 55 Conversely, low FeNa has also been observed in patients with biopsy proven ATN, 56 so urinary sodium and FeNa are no longer part of the diagnostic criteria of AKIHRS. Studies in patients without liver disease have found that fractional excretion of urea is superior to FeNa in differentiating AKIHRS from ATN in patients taking diuretics.…”
Section: Differential Diagnosis and Biomarkersmentioning
confidence: 99%
“…Error! Bookmark not defined., 25 Additional factors decrease the utility of sCr measurements in HRS-AKI. Creatine is synthesized in the liver prior to storage in muscles, where it is phosphorylated to creatinine (Cr).…”
Section: Accepted Articlementioning
confidence: 99%
“…Alsaad and colleagues mentioned that FeNa <1% in HRS was not accurate. But the test had high sensitivity and high negative predictive value, indicating that HRS diagnosis can be excluded in patients with negative test results (if FeNa more than 1%) [23].…”
Section: Diagnosismentioning
confidence: 98%